Formation of NifA-PII complex represses ammonium-sensitive nitrogen fixation in diazotrophic proteobacteria lacking NifL - Zeng, Yan; Guo, Lu; Gao, Yongqiang; Cui, Lingwei; Wang, Mengmei; Huang, Lu; Jiang, Mingyue; Liu, Ying; Zhu, Yaxin; Xiang, Hua; Li, De-Feng; Zheng, Yanning (Cell reports (Cambridge), 2024)
Biological nitrogen fixation catalyzed by nitrogenase contributes greatly to the global nitrogen cycle. Nitrogenase expression is subject to regulation in response to nitrogen availability. However, the mechanism through which the transcriptional activator NifA regulates nitrogenase expression by interacting with PII nitrogen regulatory proteins remains unclear in diazotrophic proteobacteria lacking NifL. Here, we demonstrate that in Rhodopseudomonas palustris grown with ammonium, NifA bound deuridylylated PII proteins to form an inactive NifA-PII complex, thereby inhibiting the expression of nitrogenase. Upon nitrogen limitation, the dissociation of uridylylated PII proteins from NifA resulted in the full restoration of NifA activity, and, simultaneously, uridylylation of the significantly up-regulated PII protein GlnK2 led to the increased expression of NifA in R. palustris. This insight into how NifA interacts with PII proteins and controls nitrogenase expression sets the stage for creating highly efficient diazotrophs, reducing the need for energy-intensive chemical fertilizers and helping to diminish carbon emissions. [Display omitted] •NifA is subject to transcriptional and posttranslational regulation in diazotrophs•The increased expression of fully active NifA is primarily stimulated by uridylylated GlnK2•Deuridylylated PII proteins inhibit NifA activity by forming NifA-PII complex•Deuridylylated PII proteins interact with both GAF and AAA+ domains of NifA protein Zeng et al. report that the formation of an inactive NifA-PII complex inhibits the biological nitrogen fixation in diazotrophs grown with ammonium, paving the way for creating highly efficient artificial biofertilizers that contribute substantially to the reduction of carbon emissions by cutting dependence on energy-intensive chemical fertilizers.